Derechos de los consumidores y cláusulas abusivas: resolución de conflictos ante rescisión unilateral de contratos por adhesión - Luzardo Anzoátegui, Karelis Alexa (2025)
Termination has a regulation that applies to contracts that, despite complying with legal requirements and without defects, cause significant damage to one of the parties or a third party. In the case of Ecuadorian legislation, the figure of termination is incorporated from the beginning of civil legislation, and despite not conceptualizing this legal institution, it does recognize it in its regulations. The contract in which consumers intervene leads us to have to analyze the principles that are based on classic postulates or assumptions of contractual Civil Law: which presuppose the legal equality of the parties, and then, the existence of full legal freedom between them, however in Consumer Law another reality is presented in the face of the stipulations of abusive clauses.